New Griphophanes Grootaert & Meuffels (Diptera, Dolichopodidae, Peloropeodinae) from Southeast Asia - Grootaert, Patrick; Meuffels, Henk (Zootaxa, 2012)
Five species of Griphophanes Grootaert & Meuffels are reported from Malaysia. The type species, Griphophanes grav-icaudatus (Grootaert & Meuffels) originally described from South Thailand is recorded from North Malaysia (Langkawi)as well as from South Malaysia. Three species are described from Endau Rompin National Park: G. furcatulus sp. nov.,G. furcatus sp. nov. and G. obscurus sp. nov. Griphophanes tiomanensis sp. nov. is described from the island of Pulau Tioman. A key to the species of Southeast Asia is given.